2014
DOI: 10.1007/s11102-014-0601-x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary imaging findings in male patients with hypogonadotrophic hypogonadism

Abstract: This study suggests that the use of routine hypothalamic-pituitary imaging in the evaluation of IHH, in the absence of clinical characteristics of other hormonal loss or sellar compression symptoms, will not increase the diagnostic yield of sellar structural abnormalities over that reported in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
2
9
1
1
Order By: Relevance
“…The role of total T as a hallmark of possible pathologic MRI findings in secondary hypogonadal patients has been previously considered by a limited number of studies [8,[14][15][16][17][18][19] and, among these, only one have recognized a threshold for total T [8]. This latter study has the value to have attempted a formal approach for establishing a threshold, by evaluating the difference in the frequency of abnormal computed tomography (CT) or MRI findings among total T quintiles.…”
Section: Discussionmentioning
confidence: 99%
“…The role of total T as a hallmark of possible pathologic MRI findings in secondary hypogonadal patients has been previously considered by a limited number of studies [8,[14][15][16][17][18][19] and, among these, only one have recognized a threshold for total T [8]. This latter study has the value to have attempted a formal approach for establishing a threshold, by evaluating the difference in the frequency of abnormal computed tomography (CT) or MRI findings among total T quintiles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found no differences in the frequency of low gonadotropin levels, type of amenorrhea, or presence of secondary sex characteristics when comparing patients with space-occupying lesions and those with normal pituitary MRI results. To date, several studies have reported the diagnostic usefulness of pituitary MRI in patients with HH; however, all of these studies were performed in male patients with hypogonadism [13141516]. To the best of our knowledge, this was the first study to present the frequency of pituitary MRI abnormalities and associated factors in female patients with HH.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of large space-occupying lesions in the H-P area is important, because some of the lesions can lead to neurologic sequelae such as bitemporal hemianopia or unilateral optic atrophy due to the compression of the optic chiasm or optic nerve tracts. Reassuringly, however, studies performed in male patients with HH showed a low frequency of clinically significant macroadenoma in the H-P area (0–2.4%) [13141516]. In 1996, a prospective study of 164 male patients with HH demonstrated the prevalence of total H-P imaging abnormalities and pituitary macroadenoma to be 6.7% (11/164) and 2.4% (4/164), respectively [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pituitary “incidentalomas”, usually 6 mm diameter or less, are present on magnetic resonance imaging (MRI) in about 10% of the general population, and silent adenomas are found in up to 20% of autopsies (54). In our opinion pituitary MRI, preferably with and without contrast, should be performed in men with secondary hypogonadism who meet one of the following criteria (19,55-57): severe secondary hypogonadism (total testosterone level <150 ng/dL) with FSH and LH levels below normal, signifying a higher risk of pituitary pathology, persistent hyperprolactinemia, symptoms of headache or visual defects, or in the event that any other pituitary hormones are deficient on biochemical analysis.…”
Section: The Role Of Pituitary Imagingmentioning
confidence: 99%